Development of ready to use therapeutic food for the treatment of malnutrition - Shahbuddin, Munira; Abdul Rahim, Muhammad Muiz; Jami, Mohammed Saedi; Abdullah Sani, Muhammad Shirwan; Jaswir, Irwandi (2018)
Purpose/Objectives: The reliance of poor, developing nation with severe and acute malnutrition conditions on imported processed foods is a concern. There is a need to develop a different product, that is non-peanut and non-dairy based for the treatment of malnutrition. The purpose of this invention is to break the patent and monopoly issues and to encourage local innovation and production, as well as to spur economic growth and activities in sustainable ecosystem to protect and improve lives and environment.